(untitled) (Revista Innova Educación, 2019)
The objective of the research was to determine the effect of the application of the DEPREPCEP Program in the learning of basic gymnastics in girls of the Puno 2009 Initial Educational Institution. The methodology corresponds to an experimental-level study of the application type, with a design of pre and post test of a single group. The study population was of 60 girls of 5 years and the sample of 30. For the data analysis, percentage statistics were applied and for the verification of the hypothesis the Student T statistical test. The results showed, before the application of the program 100% obtained a bad qualification in inverted vertical with support of head, vertical inverted, blade of mill and bow or spider and 97% in bearings. Afterwards, 63% of the girls obtained excellent qualification in spider arch, 60% inverted vertical, 53% short forward and backward movement and 50% windmill blade. Results that show significant difference (p = 0.000) between the level of pre and post test learning. Therefore, it is concluded that: the DEPREPCEP Program is effective in learning basic gymnastics in girls in early childhood education.